2022
DOI: 10.1371/journal.pone.0275090
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA barcoding of mosquito species (Diptera: Culicidae) in Thailand

Abstract: The correct identification of mosquito species is important for effective mosquito vector control. However, the standard morphological identification of mosquito species based on the available keys is not easy with specimens in the field due to missing or damaged morphological features during mosquito collections, often leading to the misidentification of morphologically indistinguishable. To resolve this problem, we collected mosquito species across Thailand to gather genetic information, and evaluated the DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 72 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Due to their low interspecific differences, it is impossible to distinguish between Lt. fuscana and Lt. halifaxi . The barcoding gap is a hiatus of difference between the greatest intraspecific genetic distance and the smallest interspecific distance, which is very important in determining the success of DNA barcoding [ 3 ]. Our assessment of genetic divergences revealed that this gap was not present between Lt. fuscana and Lt. halifaxii , indicating that the DNA barcoding method could not discriminate between the two species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to their low interspecific differences, it is impossible to distinguish between Lt. fuscana and Lt. halifaxi . The barcoding gap is a hiatus of difference between the greatest intraspecific genetic distance and the smallest interspecific distance, which is very important in determining the success of DNA barcoding [ 3 ]. Our assessment of genetic divergences revealed that this gap was not present between Lt. fuscana and Lt. halifaxii , indicating that the DNA barcoding method could not discriminate between the two species.…”
Section: Discussionmentioning
confidence: 99%
“…The total genomic DNA of the mosquitoes was extracted from 4 to 6 legs of each adult Lutzia specimen, using FavorPrep™ Mini Kits (Favorgen Biotech, Ping-Tung, Taiwan), following the manufacturer’s guidelines. Both universal barcode primers, including forward (5′-GGA TTT GGA AAT TGA TTA GTT CCT T-3′) and reverse (5′-AAA AAT TTT AAT TCC AGT TGG AAC AGC-3′) primers [ 38 ], were used to amplify a 709-bp fragment of COI ; the polymerase chain reaction (PCR) reaction mixture and PCR conditions were as described in a previous study [ 3 ]. Negative (water without DNA) and positive controls (DNA of Lutzia mosquitoes) were included in each PCR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method is limited by the need for complete morphological specimens and practitioner expertise [ 10 ]. Currently, effective alternative methods for species identification include geometric morphometrics and DNA barcoding; both may support the standard method to accurately identify mosquito samples that are morphologically similar [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%